From Crisis to Resilience: Pandemic Perspectives on College Student Experiences, Motivation and Self-Regulated Learning - Diana Botnaru; Anna Brady; Dragos Amarie; April Garrity; Erica Hillsnipe; Caroline Hopkinson; Cynthia Lynes; Eryn Maher (International Journal for the Scholarship of Teaching and Learning)
The short-term effects during the transition to emergency remote teaching at the onset of the COVID-19 pandemic on college students are well-studied. The present study investigated the ongoing impact of the COVID-19 pandemic on students enrolled in undergraduate classes (e.g., pandemic experiences and their impact on basic psychological needs, metacognitive learning strategies, and motivation regulation). The survey was administered at a 4-year university in the Southeastern United States during fall 2022. The majority of participants (N = 590) were women (82%), white (56.6%), not Hispanic or Latinx (93.4%), and health profession majors (58.1%). Results indicated that mental health, academic, and social experiences during the pandemic predicted students’ basic psychological need satisfaction. In turn, basic psychological need satisfaction predicted metacognitive and motivation regulation strategies. Qualitative analyses revealed that students perceived the pandemic’s influence as positive and negative. These findings highlight the variety of student experiences during the pandemic.